TINJAUAN ULANG (REVIEW) TINJAUAN TENTANG Nepenthes (NEPENTHACEAE) DI INDONESIA [A Review of Nepenthes (Nepenthaceae) in Indonesia] - Muhammad Mansur (BERITA BIOLOGI, 2013)
Nepenthes spp. (pitcher plants) are carnivorous plants, because it can trapping and digesting insects and other small animals in their pitcher as their food. In 1996, there were 80 species noted in the world. Nowadays, the number has increased up to 139 species and 68 species(48.9%) of whom live and grow on various islands in Indonesia, such as Sumatra (34 species), Kalimantan (22 species), Java (3 species), Sulawesi (11 species), Maluku (3 species) and Papua (11 species). Herbarium Bogoriense-Research Center for Biology-The Indonesian Institute of Sciences (LIPI), as the central storage plant specimens in Indonesia, currently holds 2135 sheets of 72 species of Nepenthes are collected from various islands in Indonesia and from other countries. This paper will review the current number of Nepenthes and its distribution in various islands in Indonesia.